Cryptococcus‐like changes in the setting of vasculitis. (27th November 2018) - Fresco, Amber; Wang, Jenny; Krausz, Aimee; Chan, Aegean; Franco, Loren; Garelik, Jessica; Gatica, Michelle; Balagula, Yevgeniy; McLellan, Beth; Jacobson, Mark; Amin, Bijal
Abstract : Cutaneous vasculitis has many underlying causes, and the clinical and histological findings often overlap. Inflammatory vasculitis can mimic infection; however, distinction is critical for the timely institution of appropriate therapy. We present two patients who had generalized polymorphous eruptions whose cutaneous pathology showed vasculitis with unusual haloed yeast‐like cells within the inflammatory infiltrate, mimicking Cryptococcus . The unusual cells stained negatively with Gomori methenamine silver and periodic acid‐Schiff fungal stains, but positively for CD68 and had cytoplasmic reactivity with antibody to myeloperoxidase (MPO). Both patients had positive serum anti‐MPO antibodies. The first patient experienced a rapidly fatal course, whereas the second patient improved with prompt initiation of systemic corticosteroids. Interestingly, the second case had prior biopsy showing Sweet syndrome with crypotoccoid‐appearing cells. Cryptococcoid cells have been described previously in association with neutrophilic dermatoses, but not in the setting of vasculitis as was seen in our patients. Our cases add to the existing literature on crypotoccoid mimickers, and are the first to be reported in association with vasculitis.